Rare earth ion size dependence of the Tcof the "RE-123" HTSC within the (d + s)-wave description of their superconducting state - I. M. Tang (2018)
The dependence of the Tc's on the radius of the rare earth ions in the rare earth "123" high temperature superconductors (HTSC) is explained within the framework of a (d + s)-wave model of superconductivity. The appearance of a s-wave symmetry component in the order parameter of a spin fluctuation mediated d-wave superconductor is taken to be due to the orthorhombic distortion which occurs in these HTSC. It is assumed that the structural (orthorhombic) distortion induces a corresponding anisotropy in the pairing interaction, resulting in a nonseparable anisotropic interaction. It is shown that the Tc's are affected by the orthorhombic distortion which in turn is observed to depend on the size of the RE ions. © 1998 Elsevier Science B.V.